A DESCRIPTIVE STUDY OF THE VOCABULARY MASTERY IN IDENTIFYING PREFIX AND SUFFIX OF THE SECOND GRADE STUDENTS OF SMK TELEKOMUNIKASI GENTENG - Lela Putri Fihdiya; Nur Hasibin; Wulan Wangi (LUNAR, 2023)
This research is a descriptive research about study of the vocabulary mastery in identifying prefix and suffix of the second grade students of SMK Telekomunikasi Genteng in the 2021/2022 academic year. The purpose of this research was to find the student’ ability in identifying vocabulary mastery in prefix and suffix. Students at SMK Telekomunikasi Genteng are the population. The researcher chose the second grade students of Teknik Transmisi Jaringan Department as the sample in this research. This research uses a quantitative descriptive method. The instrument used in this research was a multiple choice test. The results showed that the students’ ability in identifying students’ vocabulary mastery in prefix is “good“, categorized with a total of 65,8. The results of students’ ability in identifying students’ vocabulary mastery in suffix is “average” categorized with a total 58,3. Based on the results of the research above, it can be concluded that students at SMK Telekomunikasi, especially the second grade of Teknik Transmisi Jaringan Department, have a “good” category in prefix, it means the students have already understood about some prefix vocabularies. The majority of correct prefix vocabularies place at multiple choice test number 1,9,17 such as: Exchange, input, interconnect. Furthemore, the result of suffix is “average” category, it means the students less of understanding about suffix. The majority of correct suffix vocabularies at multiple choice test number 2 such as: communication.